TEACHER’S BELIEFS ON INTEGRATING MOBILE APPLICATION IN EFL CLASSROOM - Anugrah, Nina Julia; Sumardi, Sumardi; Supriyadi, Slamet (Universitas Muhammadiyah Semarang, 2019)
21st century skills necessitate the abilities that students’ need for their career development in the current era. The utilization of Mobile Application in teaching and learning process as the integration of Information and Communication Technology in 21st century learning demands the teacher to get used of it. Hence, this study aims to investigate teacher’s belief on integrating Mobile Application in EFL classroom. To reach the objective, a case study on an individual teacher used in this research. The participant was purposively selected because she was considered as the informant who could give sufficient information to answer the research questions. The finding of this study was teacher believes that utilizing Mobile Application is very important as Mobile Application has ability to make transformation of educational aspects by making use of it to reach instructional objectives then the quality of teaching and learning will improve.